Experimental Models of Neurodegenerative Diseases: A Simple Method to Check Both Viability of Neural Tissue and Cannulae Location After Stereotaxic Surgeries - García, S. (2012)
The reagent MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, a yellow tetrazole) is reduced to formazan in living cells, giving a purple colored product. The product absorbance issusceptible to be measured at a certain wavelength by a spectrophotometer. We report in this paper the use of MTT as a suitable method for checking both the viability of neural tissues as well as the correct location of stereotaxically placed cerebral cannulae. Evidence is given that this method can be useful not only because it is a new way of utilizing a vital staining to evaluate cannulae location, but also because MTT is a simple, effective and cheaper way of assessing the arousal level of neural tissues under study. In doing so, we can effectively test the stimulatory and/or inhibitory actions of several reagents in what we finally named as MTT-micro assay on living tissues: the MTT-malt.